Neuroscience of Pavlovian Conditioning: A Brief Review - Aguado, Luis (The Spanish Journal of Psychology, 2003)
Current knowledge on the neuronal substrates of Pavlovian conditioning in animals and man is briefly reviewed. First, work on conditioning in aplysia, that has showed amplified pre-synaptic facilitation as the basic mechanism of associative learning, is summarized. Then, two exemplars of associative learning in vertebrates, fear conditioning in rodents and eyelid conditioning in rabbits, are described and research into its neuronal substrates discussed. Research showing the role of the amygdala in fear conditioning and of the cerebellum in eyelid conditioning is reviewed, both at the circuit and cellular plasticity levels. Special attention is given to the parallelism suggested by this research between the neuronal mechanisms of conditioning and the principles of formal learning theory. Finally, recent evidence showing a similar role of the amygdala and of the cerebellum in human Pavlovian conditioning is discussed.